Organ preservation with chemoradiotherapy plus local excision for rectal cancer: 5-year results of the GRECCAR 2 randomised trial. (May 2020) - Rullier, Eric; Vendrely, Véronique; Asselineau, Julien; Rouanet, Philippe; Tuech, Jean-Jacques; Valverde, Alain; de Chaisemartin, Cecile; Rivoire, Michel; Trilling, Bertrand; Jafari, Mehrdad; Portier, Guillaume; Meunier, Bernard; et al.
Summary: Background: GRECCAR 2 was the first multicentre, randomised trial to compare local excision with total mesorectal excision in downstaged low rectal cancer. Encouraging oncological results were noted at 3 years' follow-up but needed to be corroborated with longer follow-up. In this study, we aimed to report the 5-year oncological outcomes, including local recurrence, metastatic disease, and survival. Methods: Patients age 18 years and older with T2T3 low rectal cancer, of maximum size 4 cm, who were clinically good responders after chemoradiotherapy (residual tumour ≤2 cm) were randomly assigned before surgery to either local excision or total mesorectal excision. Randomisation was centralised and not stratified and used permuted blocks of size eight. In the local excision group, a completion total mesorectal excision was performed if pathological tumour stage was ypT2–3. The primary objective of this study was to assess the 5-year oncological outcomes of local recurrence, metastatic disease, disease-free survival, overall survival, and cancer-specific mortality, which were the secondary endpoints of GRECCAR 2. We used Kaplan-Meier estimates and Cox modelling to estimate and compare recurrence and survival in modified intention-to-treat and as-treated populations. This trial was registered with ClinicalTrials.gov, number NCT00427375 . Findings: Between March 1, 2007, and Sept 24, 2012, 148 patients who were good clinical responders were randomly assigned to treatment, three patients were excluded after randomisation (because they had metastatic disease, tumour >8 cm from anal verge, or withdrew consent), leaving 145 for analysis: 74 in the local excision group and 71 in the total mesorectal excision group. Median follow-up was 60 months (IQR 58–60) in the local excision group and 60 months (57–60) in the total mesorectal excision group. 23 patients died and five were lost to follow-up. In the local excision group, 26 had a completion total mesorectal excision for ypT2–3 tumour. In the modified intention-to-treat analysis, there was no difference between the local excision and total mesorectal excision groups in 5-year local recurrence (7% [95% CI 3–16] vs 7% [3–16]; adjusted hazard ratio [HR] 0·71 [95% CI 0·19–2·58]; p=0·60), metastatic disease (18% [CI 11–30] vs 19% [11–31]; 0·86 [0·36–2·06]; p=0·73), overall survival (84% [73–91] vs 82% [71–90]; 0·92 [0·38–2·22]; p=0·85), disease-free survival (70% [58–79] vs 72% [60–82]; 0·87 [0·44–1·72]; p=0·68), or cancer-specific mortality (7% [3–17] vs 10% [5–20]; 0·65 [0·17–2·49]; p=0·53). Interpretation: The 5-year results of this multicentre randomised trial corroborate the 3-year results, providing no evidence of difference in oncological outcomes between local excision and total mesorectal excision. Local excision can be proposed in selected patients having a small T2T3 low rectal cancer with a good clinical response after chemoradiotherapy. Funding: National Cancer Institute of France.